The Optimization of Savonius Helix Wind Turbine Cut-in Speed with the Variation of Blades-twist Rotor and Number of Blades - Prabowo, Handy; Wijayanto, Danar Susilo; Saputra, Taufik Wisnu; Bakar, Mohd. Shafie bin (JIPTEK: Jurnal Ilmiah Pendidikan Teknik dan Kejuruan, 2023)
Wind turbines are typically classified as Horizontal Axis Wind Turbines (HAWT) or Vertical Axis Wind Turbines (VAWT). VAWT has a superior ability to accelerate from rest to rotation than HAWT, allowing it to rotate the rotor even when the wind speed is low; additionally, the produced torque is relatively high. Using the Savonius helix VAWT is one of the numerous methods for enhancing VAWT performance. The effect of the number of blades and the blade twist of the rotor or the angle of rotation of the blades on the rotor from the bottom end to the top end on the speed cut generated by the VAWT Savonius helix was investigated experimentally. Variations in the number of blades used in the study included 2 and 3 blades, as well as 90°, 180°, 270°, and 360° for the rotor twist blades. In a wind tunnel, data was collected at wind speeds ranging from 0 to 5 m/s. The best performance research results were obtained With three blades, a twist angle of 180 degrees, and a cutting speed of 1.51 m/s. By modifying the Savonius Helix VAWT design in this study, it is possible to increase the efficiency and performance of turbines, mainly when used at low wind speeds, and the potential for using wind energy as a more efficient and sustainable alternative energy source.